Pengaruh Citra Toko, Harga dan Word of Mouth Terhadap Keputusan Pembelian: Studi pada Konsumen Kopi Janji Jiwa di Sidoarjo - Rahma Nurlaila; mas oetarjo; Muhammad Yani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the impact of store image, price and word of mouth (WoM) on consumer purchasing decisions for Janji Jiwa coffee in Sidoarjo. The approach used is a quantitative method, with a population that includes the people of Sidoarjo Regency who have enjoyed Janji Jiwa coffee, aged between 17 and 56 years. Samples were taken using a non-probability sampling method with purposive sampling technique, involving 100 respondents. Data was collected using a questionnaire which was measured using a Likert scale. Data analysis was carried out with PLS-SEM using SmartPLS 3.0 software. The research results show that store image, price and word of mouth (WOM) have a significant positive influence on purchasing decisions for Janji Jiwa coffee in Sidoarjo.